2017
DOI: 10.1080/0092623x.2017.1326190
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Satisfaction, Quality of Life, and Their Association After Gender-Affirming Surgery: A Follow-up Study

Abstract: We assessed the outcomes of gender-affirming surgery (GAS, or sexreassignment surgery) 4 to 6 years after first clinical contact, and the associations between postoperative (dis)satisfaction and quality of life (QoL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 29 publications
(52 reference statements)
4
142
2
6
Order By: Relevance
“…22 A long-term study by van de Grift et al looked at postoperative satisfaction 4 to 6 years after the first clinical contact in 236 transgender patients who received gender-affirming surgery, and showed that overall satisfaction was 94% to 100% depending on the type of surgery performed. 24 The eight patients in the study (6%) who were unsatisfied with their surgery 4 to 6 years later were associated with either self-reported surgical complications or preoperative psychological symptoms. 24 In the KPNC transgender system, patients are required to have a rigorous mental health evaluation prior to pursuing surgery to determine if there are any preoperative psychological symptoms that may lead to dissatisfaction with surgery.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…22 A long-term study by van de Grift et al looked at postoperative satisfaction 4 to 6 years after the first clinical contact in 236 transgender patients who received gender-affirming surgery, and showed that overall satisfaction was 94% to 100% depending on the type of surgery performed. 24 The eight patients in the study (6%) who were unsatisfied with their surgery 4 to 6 years later were associated with either self-reported surgical complications or preoperative psychological symptoms. 24 In the KPNC transgender system, patients are required to have a rigorous mental health evaluation prior to pursuing surgery to determine if there are any preoperative psychological symptoms that may lead to dissatisfaction with surgery.…”
Section: Discussionmentioning
confidence: 95%
“…24 The eight patients in the study (6%) who were unsatisfied with their surgery 4 to 6 years later were associated with either self-reported surgical complications or preoperative psychological symptoms. 24 In the KPNC transgender system, patients are required to have a rigorous mental health evaluation prior to pursuing surgery to determine if there are any preoperative psychological symptoms that may lead to dissatisfaction with surgery. As such, many of the patients in this study also had or are scheduled for other transgender procedures.…”
Section: Discussionmentioning
confidence: 95%
“…In the literature studies found that transitioning can positively affect a person's life satisfaction through positive changes in appearance, attractiveness, body satisfaction, sex life, health-related quality of life, family and social relationships, partner relations, achievements in life, personal goals, self-confidence, identity and spirituality (van de Grift et al, 2017;Bockting et al, 2016;Costa and Colizzi, 2016;Köllen, 2016;Dhejne et al, 2016;White Hughto and Reisner, 2016;Cardoso da Silva et al, 2016;Schmidt, and Levine, 2015;Castellano et al, 2015;Ruppin and Pfäfflin, 2015;Brewster et al, 2014, Manieri et al, 2014Hess et al, 2014;Brewster et al, 2012, Salvador et al, 2012, Gorin-Lazard et al, 2012Colton-Meier et al, 2011;Johansson et al, 2010;Parola et al, 2010, Weyers et al, 2009Imbimbo et al, 2009;Nelson et al, 2009;Kraemer et al, 2008;Gijs, and Brewaeys, 2007;Lobato et al, 2006, De Cuypere et al, 2006, Smith et al, 2005Michel et al, 2002). 2013found that cross-sex hormonal treatment was linked to a better quality of life.…”
Section: Transitioning and Life Satisfactionmentioning
confidence: 99%
“…(ii) Trans people who were dissatisfied with or regretful about their gender reassignment surgery's outcomes scored lower in terms of quality of life than general populations (van de Grift et al, 2017).…”
Section: Trans People's Mental Health and Quality Of Life Before Andmentioning
confidence: 99%
See 1 more Smart Citation